Berkreasi Bersama Pembuatan Media Kantong Berhitung Berbasis Teori Bruner Bagi Guru Sekolah Dasar - Fitri, Ayu; Suparman, Tarpan; Asmara, Andes Safarandes; Fajar, Muhammad Jelang (Badranaya: Jurnal Pengabdian Kepada Masyarakat, 2024)
Improvements in information technology have created several innovative digital learning media. However, teachers often face obstacles in creating or using this media due to limited technological knowledge or inadequate facilities. As an alternative, using number-counting bags with straws might be an easier solution for teachers to practice and use in the learning process. The activity "Creating Together in Making Counting Bag Media Based on Bruner's Theory for Elementary School Teachers" aims to improve the ability of elementary school teachers to produce effective mathematics learning media. This activity involved 17 teachers from the Tunas Dharma Private Elementary School. The training process is carried out through the stages of preparation, delivery of material, creation of learning media, media presentation, and evaluation. From this training activity, it can be seen that the skills of teachers, student enthusiasm for learning, and the quality of mathematics learning in elementary schools have increased through the use of creative and effective number-counting bag media.